2019
DOI: 10.1177/0892705719868278
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of HDPE/MWCNT and HDPE/kenaf composites

Abstract: The present work deals with the microwave-assisted compression moulding of high-density polyethylene (HDPE)-based composites. In the present work, 20 wt% of reinforcement in the form of kenaf and multi-walled carbon nanotube (MWCNT) was used to fabricate HDPE/kenaf and HDPE/MWCNT polymer composites. The mechanical characterizations of the microwave-processed composites were carried out in terms of uniaxial tensile test with different strain rate, multistep stress relaxation, flexural and impact test. The uniax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The reason for the increase in the load-bearing capacity is due to a stronger phase between the matrix and the reinforcement which further increases the stiffness and modulus value of the composite. 54 A sudden increment of flexural modulus can be seen from UHMWPE/K1 and UHMWPE/K2. This is due to the presence of stacked UHMWPE between two Kevlar V R layers that acts as a Kevlar V R -Kevlar V R adhesive material providing an increase in the Van der Waals forces between the layers of Kevlar V R and UHMWPE bonded inside them.…”
Section: Flexural Testmentioning
confidence: 95%
“…The reason for the increase in the load-bearing capacity is due to a stronger phase between the matrix and the reinforcement which further increases the stiffness and modulus value of the composite. 54 A sudden increment of flexural modulus can be seen from UHMWPE/K1 and UHMWPE/K2. This is due to the presence of stacked UHMWPE between two Kevlar V R layers that acts as a Kevlar V R -Kevlar V R adhesive material providing an increase in the Van der Waals forces between the layers of Kevlar V R and UHMWPE bonded inside them.…”
Section: Flexural Testmentioning
confidence: 95%
“…[1][2][3] Moreover, HDPE is hardest member of PE family due to its linearity with a little entanglements. 4 Thanks to these superior characteristics, HDPE has a remarkable demand by several industrial sectors to produce many various materials such as daily bottles, boxes, fuel tanks of cars, packaging container, toys, carrier bag, disposable suits, wire coating, cable insulation, pipes etc. 5 Correspondingly, the global production value of HDPE is recorded as roundly 30 million tons per year.…”
Section: Introductionmentioning
confidence: 99%
“…The impact energy absorbed by the HDPE/kenaf polymer composite (1.055 J) was 81.12% higher than the HDPE/MWCNT composite (0.582 J). 37 MHT on oil palm empty fruit bunch (EFB) and glass fiber (GF) was done by Islam et al 38 Then, hybrid composites were made from microwave treated fibers and recycled polypropylene (RPP). They found that microwave-treated fiber-based composites showed improved mechanical and thermal properties compared to untreated ones.…”
Section: Introductionmentioning
confidence: 99%